Sliding the SLM-technique to Reduce the Non-Linear Distortion in OFDM Systems - Taher, M. A.; Singh, M. J.; Ismail, M. B.; Samad, S. A.; Islam, M. T. (Elektronika ir Elektrotechnika, 2013)
In this paper, a novel technique that can be effectively used to reduce the peak-to-average power ratio (PAPR) of the orthogonal frequency division multiplexing (OFDM) system is proposed. The proposed technique, called sliding selected mapping (SSLM), is considered a modified version of the conventional selected mapping (CSLM) scheme. SSLM uses a window with a predefined size of less than N, which carries the phase rotation vector (PRV). In contrast to the CSLM, SSLM uses length-f·N PRVs (0<f<1). The window is shifted by a step size (sliding) on the data sequence. At each shift, the modified data sequence undergoes IFFT operations to check the PAPR, similar to the CSLM. Thereafter, the shift index that corresponds to the minimum PAPR is chosen as the side information. Meanwhile, for comparison, the CSLM uses the PRV index as side information. Simulation results and mathematical computations show that our proposed technique requires less computational complexity. In addition, the corresponding amount of side information is significantly reduced compared with that of CSLM. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.2075